Informaciniai santykių mainų aspektai - Rytel, Tomas (Information & Media, 2009)
Šio straipsnio tikslas – atskleisti informacijos ir komunikacijos elementų svarbą šiuolaikinėje marketingo vadyboje, informaciją suvokiant kaip esminį mainų atributą, kuris skatina sandoriais (angl. transaction) grindžiamus mainus keisti santykių (angl. relationship) mainais. Šis aprašomojo pobūdžio tyrimas yra atliktas pasitelkiant mokslinės santykių marketingo literatūros šaltinių apžvalgos ir hipotetinio pobūdžio interpretacijomis grindžiamus mokslinės kūrybos metodus. Straipsnyje siekiama pagrįsti hipotezę, jog santykių mainai tarp įmonės ir vartotojo pasireiškia kaip informacijos ir komunikacijos procesų nulemta veikla, kuria mažinamas pažinimo disonansas, užtikrinamas saugumo jausmas, emocinis pasitenkinimas informacijos turiniu ir kiekiu. Santykių mainai nagrinėjami informacijos ir komunikacijos aspektais, siekiant atskleisti jų svarbą marketingo vadyboje. Informacija interpretuojama kaip esminė šiuolaikinės marketingo vadybos kategorija, nuo kurios valdymo priklauso būsima mainų tarp įmonės ir vartotojo forma bei mainų trukmė. Kintančio sociumo kontekste marketingas gali būti apibrėžiamas kaip informacijos procesų nulemta veikla, kuri leidžia didinti žinojimą apie rinką ir joje veikiančius dalyvius, šias žinias naudojant vertybiniams vartotojų bruožams nustatyti ir jomis remiantis kurti vertę rinkoje. Reikšminiai žodžiai: informacijos valdymas, komunikacija, dialogas, santykiai, socialinis emocinis ryšys. Informational aspects of relationship exchange in marketing Tomas Rytel Summary The article aims at rationalizing a hypothesis that exchange of relations between a company and a user occurs as an activity conditioned by informational and communicational processes, which reduces cognitive dissonance and guarantees the feeling of safety and emotional satisfaction in terms of the content and amount of information. Information is interpreted as a basic category of modern marketing management, which influences the future swap between a company and a user as well as the duration of exchanges. Needs of current users may be approached as natural demand of a person for information, materialization of which in terms of content and amount enables to reduce cognitive dissonance in market exchanges. By applying postmodernistic discourse in the context of marketing management, the basic factor generating market-based exclusiveness and competitiveness (or an element of the value-establishing chain) is the know-how, and the main resource is information; thus, from the economic point of view, success or failure of any kind of business depends not on its production efficiency, but on the ability to involve the creative potential and know-how. An increasing need for brands and symbols in marketing prompts to satisfy individual expectations of users in terms of the content and amount of information. Users in today’s market are being governed by a great number of rapidly changing symbols which are being created in terms of the content and amount of information. The performed research has confirmed that relationship exchange is being generated as an activity determined by information and communication, which may change even the very conception of marketing management. The scientific problem discussed in the paper effectuates the following conclusions: 1. Relations are being interpreted as an activity determined by verbal and non-verbal communication, which stimulate information spread, en courage a user to trust a company, minimize the search of alternatives, and increase loyalty towards a company, its products / services or brand name. 2. Relationship exchanges appeal to the maximally individual relationship between a user and a company, which may occur only in the presence of the feeling of reliability and obligation, which is being generated as permanent phenomena of information exchange. These facts act as the basis for interpreting information and communication as a significant category of exchanges, which under participation in the process of exchange is likely to reduce formal separation and to increase the interdependence in terms of fellow-feeling. 3. Relations are being generated on the emotional basis which is established according to the social-economic features of exchange. The mentioned features of exchange occur when swapping not material objects, but those involving the informational features. 4. Bilateral communication is being developed, which discloses exchange as the process of information and know-how exchange capable of turning the interrelation between a company and a user into a relationship. 5. Information and know-how turn into commodity which is a value for a company and a user. Information and know-how in the modern market ensure an organic link between a company and a user and serve for the development of relations, for exchanges based on relationship, reducing formal divides, determining a communication. Key words: information management, communication, dialogue, relationship.